Prescribing quality in patients with chronic diseases at primary and secondary health care facilities using prescription quality index tool - Suthar, Jalpa V.; Patel, Varsha J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Prescribing quality is a matter of major concern worldwide. This study was carried out to determine the quality of prescribing in chronic diseases at primary health care (PHC) and secondary health care (SHC) settings using the new prescription quality index (PQI) tool. Methods: A cross-sectional observational study was carried out at four PHC and two SHC facilities in Anand district of India. Patients attending these facilities for at least 3 months were included. Complete medical history and prescriptions received were noted. Total and criteria wise PQI scores were derived for each prescription. Prescriptions were categorized as poor (score of ≤31), medium (score 32-33), and high quality (score 34-43) based on PQI total score. The internal consistency of PQI was measured using item total correlation and Cronbach’s α so as to validate it in our settings. Data were analyzed using Statistical Package for Social Science 20. Results: A total of 134 prescriptions were collected and evaluated for quality of prescribing. Mean age of patients was 60.6 ± 13.5 years. Mean PQI score was 23.60 ± 9.3 with 71.6% prescriptions being of poor quality. Quality of prescribing did not differ at PHC and SHC (P>0.05). Of 22 criteria, PQI score was strongly correlated with drug indication, drug effectiveness, evidence-based prescribing, unnecessary duplication, duration of therapy, and cost (P<0.01). PQI total score was negatively correlated to the number of drugs per prescription. Cronbach’s α for the entire 22 criteria were 0.90. Conclusion: PQI was found to be a reliable tool for assessment of prescribing quality in chronic diseases.